2019
DOI: 10.1093/omcr/omz036
|View full text |Cite
|
Sign up to set email alerts
|

Possible exercised-induced rhabdomyolysis associated with terbinafine

Abstract: Introduction. Terbinafine is reported to be associated with rhabdomyolysis. We present a patient taking terbinafine who may have developed exercise-induced rhabdomyolysis. Case Report. A healthy 40-year-old female developed onychomycosis of the right first toe for which she was taking terbinafine. After an increase in her exercise regimen, she began experiencing notable myalgias of the triceps. During outpatient evaluation, the patient was found to have elevated and worsening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…The case report documents highly elevated CK levels (4774 IU/L, against 25-155 IU/L), probably due to increased frequency of physical exercise when the patient was on terbinafine. 13 However, in the present case, the mild elevation of CK-NAC was most probably due to terbinafine use alone, as the patient reports no changes in the physical activity and fluid intake prior to, during, and after terbinafine use. The drug-induced myotoxic symptoms may appear anywhere from one week to months after initiating the offending drug and can resolve within weeks after its withdrawal.…”
Section: Discussioncontrasting
confidence: 49%
“…The case report documents highly elevated CK levels (4774 IU/L, against 25-155 IU/L), probably due to increased frequency of physical exercise when the patient was on terbinafine. 13 However, in the present case, the mild elevation of CK-NAC was most probably due to terbinafine use alone, as the patient reports no changes in the physical activity and fluid intake prior to, during, and after terbinafine use. The drug-induced myotoxic symptoms may appear anywhere from one week to months after initiating the offending drug and can resolve within weeks after its withdrawal.…”
Section: Discussioncontrasting
confidence: 49%
“…In the English literature, there are only a few case reports of terbinafine-induced rhabdomyolysis. 11 - 13 Ly et al reported a case of rhabdomyolysis due to terbinafine use and concurrent exercise; CK was elevated at 14 400 U/L. Bui et al described a similar case in the context of increased exercise intensity, and the CK was <5000 U/L.…”
Section: Discussionmentioning
confidence: 99%